(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Southeast Asia grappled with an early wave of COVID-19 cases, witnessing a spike in 2021 and early 2022 before vaccination efforts led to a decline. Governments in the region adopted diverse strategies, including lockdowns and public health measures, tailored to each country’s cultural and socioeconomic landscape. This article delves into the COVID-19 outbreak across the 11 member countries, encompassing all ASEAN nations and Timor-Leste. It highlights the region’s progression from low infection rates in 2020 to heightened mortality in 2021, followed by a drop in cases as vaccination coverage increased. Despite shared challenges, disparities in culture, wealth, and political context influenced the implementation and effectiveness of containment measures.